Endodontic management of hypertaurodontism - Puneet Jindal; Radhika Lekhi; R S Kang; Navjot Singh Khurana (Wolters Kluwer Medknow Publications, 2015)
Taurodontism is a morphological developmental abnormality of a tooth in which the body of the tooth is enlarged at the expense of roots. The condition complicates nonsurgical root canal therapy because of the complexities within the root canal system, variable canal configurations, and expecting additional root canals. The present case report describes a case of bilateral hypertaurodontism and the endodontic therapy of right mandibular hypertaurodont second molar.